Horses without doctors: why is the equine veterinarian industry facing a shortage? - Leo, Adison, author; Fedorka, Carleigh, author; Magee, Christianne, author (Colorado State University. Libraries, 2024)
It has been well documented that there is a shortage of practitioners entering the equine medicine workforce. Unfortunately, minimal research has gone into the causative agents for this shortage. Therefore, the objectives of this study were 1) to identify current concerns within the equine veterinary medicine workforce, and 2) isolate common perceptions of equine veterinary medicine within equine industry members who no longer desire to enter the workforce. To do so, 264 members of the equine industry were surveyed. These respondents could be separated into groups of 1) equine industry members (n=243) and 2) current equine practitioners (n=21). Additionally, equine industry members were further separated based on current interest in equine veterinary practice (1=very disinterested, 5=very interested). Of those responders, 197 (n=197) had lost interest in pursuing equine veterinary medicine, while 31 (n=31) maintained interest. When surveying equine veterinarians, the primary issues within their career were work-life balance (85%), mental health (70%), and debt-to-income ratio (65%). When surveying equine industry members on the perceived problems within equine veterinary medicine, the primary issues were debt-to-income ratio (66.7%), work-life balance (61.3%), and mental health (38.7). Therefore, the top three concerns in both populations were similar, although the percentage of respondents indicating concern varied widely. When further assessing only respondents that had lost interest, the primary concerns were cost of education (61.1%), length of education (69.6%), income after graduation (49.2%), and feeling as though their grades are not suitable for acceptance (35.4%). In conclusion, it appears that the general equine industry populace is aware of the current problems within the career of equine veterinary medicine (see figure 2). As low income alongside poor mental health and a lack of work-life balance are the primary issues, these 3 aspects within equine veterinary medicine need to be addressed in order to improve the equine veterinary medicine shortage.
College of Agriculture Sciences/Equine Science/University Honors Program/Adison Leo, Dr. Carleigh Fedorka, Dr. Christianne Magee.
Keywords: shortage; equine; veterinarian